Effect of Zirconia Thickness on the Tensile Stress of Zirconia Based All-Ceramic Restorations - Masood Shiezadeh; Mahdie Seyf; Hamid Reza Rajati; Asadolah Karazhian; Pouria Mohammadparast (Mashhad University of Medical Sciences, 2015)
Introduction: The purpose of the presented study was to evaluate the effect of zirconia thickness on the tensile stress of zirconia based all-ceramic restorations. Methods: Twenty zirconia disks with 10mm diameter were prepared in two groups using CAD/CAM system. The thickness of zirconia was 0.5mm in first group and 0.3mm in second group. After sintering, 0.4mm glass ceramic porcelain was applied to each disk. Then, sintering and glazing of porcelain carried out. Instron testing machine with 1mm/min crosshead speed used to evaluate the failure load of the samples. Biaxial Flexural strength standard formula employed to calculate tensile stress of specimens. Statistical analysis performed using SPSS software. Results: Although data analysis showed more maximum tensile stress in 1st group, no significant differences were found between two groups. Conclusion: Zirconia with 0.5mm and 0.3mm thicknesses cause similar tensile stress in all-ceramic restorations and thickness of these laminates could be reduced to 0.7mm.